M-health for maternal health- bridging the gaps!! - Marwah, Sheeba; Mittal, Pratima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This article reviews significance, potential and principles to consider when setting up a telemedicine (TM) program to provide care to women in the field of obstetrics and gynecology, essentially deploying mobile technology. There are various benefits of such TM clinical applications. The consensus among patients and health care providers is that this technology is convenient to provide needed subspecialty medical care, even when it is not available locally. Such innovations are clinically successful, but economic and cost-effectiveness data are lacking.